Reconsidering Toxoplasmosis Prevention and Treatment Due to Its Relation to Neuropsychiatric Disturbances - Fabrizio Bruschi; Silvia Fabiani (Zoonotic Diseases, 2025)
Toxoplasmosis is a parasitic, foodborne infection caused by Toxoplasma gondii. The infection can be transmitted through various routes, including the following: (i) the consumption of vegetables, fruits, or drinking water containing sporulated oocysts; (ii) the consumption of raw or undercooked meat; (iii) transmission from mother to fetus; (iv) through blood transfusion; and (v) transplantation of solid organs, bone marrow, or hematopoietic stem cells. Infection is generally asymptomatic or exhibits a mild clinical presentation in those with adequate immune function; however, the clinical outcomes becomes more severe in both fetal and immunocompromised individuals. In this work, we reviewed the current literature, primarily focusing on epidemiological and neurobiological aspects. Using the PubMed database, we conducted a search by combining the following terms: “Toxoplasma gondii” or “Toxoplasmosis” and “neuropsychiatric” “diseases” or “disorders” or “psychiatric” “diseases” or “disorders” or “neurological” “diseases” or “disorders” or “neurobehavioral disorders” or “behavioral disorders” or “schizophrenia” or “bipolar disorder” or “autism spectrum disorder” or “Parkinson’s disease” or “Alzheimer’s disease”. No language or time restrictions were applied in the literature review, which was concluded in April 2024. Although the literature does not yet provide definitive answers, current data should be considered sufficient to change attitudes toward toxoplasmosis prevention and treatment measures. The focus should be not only with regard to seronegative pregnant women and immunocompromised patients, but also to people particularly prone to developing neuropsychiatric diseases.